Fabrication of dual-functional composite yarns with a nanofibrous envelope using high throughput AC needleless and collectorless electrospinning - Valtera, Jan; Kalous, Tomas; Pokorny, Pavel; Batka, Ondrej; Bilek, Martin; Chvojka, Jiri; Mikes, Petr; Kostakova, Eva Kuzelova; Zabka, Petr; Ornstova, Jana; Beran, Jaroslav; Stanishevsky, Andrei; et al. (Scientific reports, 2019)
Nanotechnologies allow the production of yarns containing nanofibres for use in composites, membranes and biomedical materials. Composite yarns with a conventional thread core for mechanical strength and a nanofibrous envelope for functionality, e.g. biological, catalytic, have many advantages. Until now, the production of such yarns has been technologically difficult. Here, we show an approach to composite yarn production whereby a plume of nanofibers generated by high throughput AC needleless and collectorless electrospinning is wound around a classic thread. In the resulting yarn, nanofibres can form up to 80% of its weight. Our yarn production speed was 10 m/min; testing showed this can be increased to 60 m/min. After the yarn was embedded into knitwear, scanning electron microscope images revealed an intact nanofibrous envelope of the composite yarn. Our results indicate that this production method could lead to the widespread production and use of composite nanofibrous yarns on an industrial scale.